Proceso de atención de enfermería en paciente pediátrico con diagnóstico de neumonía adquirida en la comunidad: un estudio de caso - Morejón Avalos , Washington David (2024)
Pneumonia is an acute infection of the lung parenchyma, usually caused by Streptococcus pneumoniae, and is quite common in the pediatric community. The main objective of this study was to design an individualized nursing care plan, based on NANDA, NOC, and NIC taxonomies, to optimize care and improve the quality of life of the pediatric patient with pneumonia. The health status assessment was conducted using Marjory Gordon’s functional health patterns model, which allowed the identification of altered patterns requiring urgent intervention, such as ineffective breathing pattern, activity intolerance, and ineffective airway clearance. Based on this assessment, specific interventions were implemented, focusing on airway management, oxygen administration through a nasal cannula, respiratory therapies, and play-based techniques to encourage deep breathing, all essential in pediatric management. The methodology included continuous monitoring of NOC indicators, such as airway patency, fever reduction, and stabilization of respiratory and heart rates. These indicators were key to adjusting interventions according to the patient’s clinical progress. The results showed a significant improvement in health status, with a notable reduction in respiratory symptoms and an improved response to treatment, reflecting the effectiveness of the applied interventions.